Implementasi Kebijakan Manajemen Risiko Terhadap Stabilitas dan Kinerja Keuangan Suatu Perusahaan - Nabila Zahara; Nanda Nurul Atika; Sekar Widyamada Pitaloka; Syavina Nadhira Lubis; Arsyadona A (Madani: Jurnal Ilmiah Multidisiplin, 2025)
With the rapid development of the global economy in a company, of course, it will not avoid a risk. Risk is an adverse consequence caused by unforeseen circumstances, and is an uncertainty relating to prospective profits or losses. The purpose of this article is to gain an in-depth understanding of the effect of risk management policies on the stability and financial performance of the company. Which is where this research uses a literature study approach (library research) which focuses on theoretical analysis of various relevant literature sources. The results can be seen that the implementation of risk management policies in general makes a positive contribution to the stability and financial performance of the company. Despite the positive impact, there are challenges or obstacles in its implementation, including very complex costs, as well as regulations that are constantly changing. However, with the right strategies and steps the company can handle this and can minimize risk.